2020
DOI: 10.1002/ange.202012304
|View full text |Cite
|
Sign up to set email alerts
|

Arrested Substrate Binding Resolves Catalytic Intermediates in Higher‐Plant Water Oxidation

Abstract: Among the intermediate catalytic steps of the water‐oxidizing Mn4CaO5 cluster of photosystem II (PSII), the final metastable S3 state is critically important because it binds one substrate and precedes O2 evolution. Herein, we combine X‐ and Q‐band EPR experiments on native and methanol‐treated PSII of Spinacia oleracea and show that methanol‐treated PSII preparations of the S3 state correspond to a previously uncharacterized high‐spin (S=6) species. This is confirmed as a major component also in intact photos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 45 publications
(34 reference statements)
1
13
4
Order By: Relevance
“…This is a different assignment to that previously made for the S=6 form detected in spinach samples where the S=6 form was attributed to a closed cubane form of the WOC cluster with a pentacoordinated Mn 4 (IV) ionan intermediate formed prior to binding of the second substrate water. 25 This however, in striking contrast to the model proposed here, is not supported by the XFEL structural data. 23 In addition it has been shown that Mn(III) is required for NIR excitation 30 and the large D value of 1.523 cm -1 for the S=6 form strongly suggests the presence of Mn(III) ion in the complex.…”
Section: Crystallographic and Electron Paramagnetic Resonance Analysiscontrasting
confidence: 88%
See 2 more Smart Citations
“…This is a different assignment to that previously made for the S=6 form detected in spinach samples where the S=6 form was attributed to a closed cubane form of the WOC cluster with a pentacoordinated Mn 4 (IV) ionan intermediate formed prior to binding of the second substrate water. 25 This however, in striking contrast to the model proposed here, is not supported by the XFEL structural data. 23 In addition it has been shown that Mn(III) is required for NIR excitation 30 and the large D value of 1.523 cm -1 for the S=6 form strongly suggests the presence of Mn(III) ion in the complex.…”
Section: Crystallographic and Electron Paramagnetic Resonance Analysiscontrasting
confidence: 88%
“…Also shown are simulations for an S=6 form using the zero field splitting parameters reported for the spinach samples. 25 From the simulations it is clear that the spectral intensity of the S= 6 form is much less than that of the S=3 form. This suggests that the S=6 form would be difficult to detect in the Wband EPR experiment.…”
Section: Crystallographic and Electron Paramagnetic Resonance Analysismentioning
confidence: 90%
See 1 more Smart Citation
“…Nevertheless the non-detection of these two forms of S 3 by X-band EPR, it seems unlikely that they correspond to the EPR invisible S 3 mentioned above. Indeed, the new S 3 signals described in [46, 47] are detectable in the presence of glycerol and methanol, whereas the formation of the (S 2 Tyr Z ● )’ state upon a near-IR illumination in the centers in S 3 defined as EPR invisible is inhibited in the presence of glycerol (and in the presence of methanol in plant PSII) [48, 49]. Finally, computational works also suggested heterogeneities in S 3 [5052] with also a S = 6 spin value [52, 53].…”
Section: Introductionmentioning
confidence: 99%
“…With X-and Q-band EPR experiments performed in the S 3 -state of plant PSII, both in the perpendicular and parallel modes, a high-spin, S = 6, was shown to coexist with the S = 3 configuration. This S = 6 form was attributed to a form of S 3 without O6/Ox bound and with the Mn IV part of the cluster in ferromagnetic interaction with the unsaturated dangler Mn IV [48]. Nevertheless these two forms of S 3 are not detected by X-band EPR, it seems unlikely that they correspond to the EPR invisible S 3 mentioned above.…”
Section: Introductionmentioning
confidence: 99%